Kinase Inhibitors as Potential Therapeutic Agents in the Treatment of COVID-19 - Naik, Rajashri R.; Shakya, Ashok K.; Aladwan, Safwan M.; El-Tanani, Mohamed (Frontiers in Pharmacology, 2022)
Corona virus is quickly spreading around the world. The goal of viral management is to disrupt the virus’s life cycle, minimize lung damage, and alleviate severe symptoms. Numerous strategies have been used, including repurposing existing antivirals or drugs used in previous viral outbreaks. One such strategy is to repurpose FDA-approved kinase inhibitors that are potential chemotherapeutic agents and have demonstrated antiviral activity against a variety of viruses, including MERS, SARS-CoV-1, and others, by inhibiting the viral life cycle and the inflammatory response associated with COVID-19. The purpose of this article is to identify licensed kinase inhibitors that have the ability to reduce the virus’s life cycle, from entrance through viral propagation from cell to cell. Several of these inhibitors, including imatinib, ruxolitinib, silmitasertib, and tofacitinib (alone and in conjunction with hydroxychloroquine), are now undergoing clinical studies to determine their efficacy as a possible treatment drug. The FDA approved baricitinib (a Janus kinase inhibitor) in combination with remdesivir for the treatment of COVID-19 patients receiving hospital care in November 2020. While in vitro trials with gilteritinib, fedratinib, and osimertinib are encouraging, further research is necessary before these inhibitors may be used to treat COVID-19 patients.